Akibat Hukum Wanprestasi dalam Transaksi Jual Beli Online Perspektif KUHPerdata dan UU ITE - Satria Wiguna; M. Salik Ruqy; Bintang Hibatullah; Yardo Dafo Al Farid (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
The rapid development of information technology has significantly increased the volume of online buying and selling transactions in Indonesia. However, this growth has not been fully accompanied by adequate legal awareness among the parties in fulfilling their respective rights and obligations, resulting in various legal disputes, particularly those related to breach of contract. This study aims to analyze the forms of breach of contract in online sales transactions and examine their legal consequences under the Indonesian Civil Code (Kitab Undang-Undang Hukum Perdata or KUHPerdata) and Law Number 11 of 2008 concerning Electronic Information and Transactions (EIT Law). This research employs a normative legal research method using statutory and conceptual approaches. The findings reveal that breaches of contract in online transactions include failure to perform contractual obligations, improper performance, delayed performance, and actions that violate the agreed contractual terms. The legal consequences include the injured party's right to demand contract performance, claim compensation pursuant to Articles 1243–1252 of the Indonesian Civil Code, and seek contract cancellation under Articles 1266 and 1267 of the Civil Code. Dispute resolution may be pursued through the internal dispute resolution mechanisms provided by e-commerce platforms, the Consumer Dispute Settlement Agency (BPSK), or the District Court to ensure legal certainty and protection for the parties involved.